Comparative transcriptome analysis of the climacteric of apple fruit uncovers the involvement of transcription factors affecting ethylene biosynthesis - Li, Tong; Zhang, Xiao; Wei, Yun; Xu, Yaxiu; Liu, Weiting; Li, Hongjian; Yang, Guangxin; Wang, Aide; Wang, Xiaoxue (Horticultural plant journal, 2023)
Apple (Malus domestica) fruit generally undergoes a climacteric. During its ripening process, there is a peak in ethylene release and its firmness simultaneously decreases. Although more in-depth research into the mechanism of climacteric-type fruit ripening is being carried out, some aspects remain unclear. In this study, we compared the transcriptomes of 0-Pre and 15-Post (pre- and post-climacteric fruit), and 15-Post and 15-MCP [fruit treated with 1-MCP (1-methylcyclopropene)]. Various transcription factors, such as MADS-box, ERF, NAC, Dof and SHF were identified among the DEGs (differential gene expressions). Furthermore, these transcription factors were selected for further validation analysis by qRT-PCR. Moreover, yeast one hybrid (Y1H), β-glucuronidase (GUS) transactivation assay and dual-luciferase reporter assay showed that MdAGL30, MdAGL104, MdERF008, MdNAC71, MdDof1.2, MdHSFB2a and MdHSFB3 bound to MdACS1 promoter and directly regulated its transcription, thereby regulating ethylene biosynthesis in apple fruit. Our results provide useful information and new insights for research on apple fruit ripening.